Improving Knowledge in Efforts to Prevent Worm Infections Among Elementary School Students at SD 007 Samarinda - Nintra Mahdan Liranti; Alda Azmi; Islamudin Ahmad (B-Creta Publisher, 2026)
Background: Helminthiasis remains a public health issue in Indonesia, particularly among school-aged children due to frequent exposure to contaminated environments. Although the national prevalence decreased to 31.8% in 2016, a case study at SDN 007 Samarinda in 2018 showed a 100% prevalence of helminth infection in students’ fingernail samples, predominantly caused by Ascaris lumbricoides, indicating poor sanitation and personal hygiene. Objective: This outreach activity aimed to increase the knowledge and awareness of 27 students regarding the causes, risks, and prevention of helminthiasis, and to promote the adoption of clean and healthy living behaviors (PHBS). Methods: The program included lectures explaining helminthiasis and its prevention, followed by a live demonstration of proper handwashing techniques. Effectiveness was measured through student enthusiasm and by comparing pre-test and post-test scores. Results: There was a significant improvement in students' knowledge, with the average correct answers rising from 59.3% (pre-test) to 97.8% (post-test). The number of students classified with high knowledge increased from 25.9% to 96.3%. Conclusion: The educational intervention proved highly effective in enhancing health literacy and motivating preventive behavior against helminthiasis among elementary school students.